Mechanisms of stress-overcoming behavior in women with oncopathology - Bohdan Stanovskiy (Kazimierz Wielki University, 2023)
The article describes the empirical research of the features of stress coping behavior in patients with newly diagnosed oncopathology. The author's attention is directed to the analysis of the chronic social stress impact on the psychological state of women with cancer due to its relevance in modern social conditions. The article highlights the hypothesis that the effectiveness of stress coping behavior and the general psychological state of patients are closely related to the quality and specificity of provided psychological support. Particular attention is paid to the study of the connection between individual strategies for stress coping and social factors, in particular, family support, dealing with friends and medical personnel. The research is based on an interdisciplinary approach, including knowledge from medicine, psychology, sociology, and other fields for a deeper understanding of the mechanisms of stress coping behavior in patients with oncology and the development of a comprehensive support strategy considering a wide range of factors: from individual characteristics to social living conditions. The conclusions of the empirical study are important for the practice of medical psychology and further research in the field of psycho-oncology.